Fatal pulmonary embolism or bleeding in patients with venous thromboembolism: implications of real-life data. Issue 181 (September 2019) - Monreal, Manuel
ABSTRACT: Reliable information on what patients with venous thromboembolism (VTE) are at increased risk to die of pulmonary embolism (PE) or bleeding (and the time course of the two fatal events) could likely help to better use anticoagulant therapy by improving selection of patients in whom its benefit will likely outweigh the risk. Unfortunately, there is scarce information in the literature on the incidence and time-course of fatal PE and fatal bleeding in real life clinical practice. This review article provides an overview of the most important published data on this topic using the RIETE (Registro Informatizado de Enfermedad Trombo Embólica) registry.